A study of the actual results of the strategic analysis (S.W.O.T) of sports activities within the student activities divisions and units of Baghdad's universities (Journal of Humanities and Social Sciences Research, 2023)
This study establishes a Strategic Analytical Measure for Conducting Sports Activities (S.W.O.T) for Faculty and Units of Student Activities in Universities of the University of Baghdad, considering the importance and effects of sports activities in Iraqi universities. and intended to apply to the study sample. Role in student development in all aspects: social, engaged, collaborative and otherwise. The study was based on an application sample of (101) people from a community of (245) people who work in the divisions and units of student activities in Baghdad universities' colleges. The questionnaire with (57) items dispersed on the four axes (strength - weakness - threats - opportunities) was used. The study's findings revealed. Sports activity has the element of strength represented by the human potential through the experiences of the members of the sports activity. Weakness among the sports activity officials and compliance with the material capabilities and the lack of interest by the deans of the faculties in the sports activity creates opportunities for improvement in the sports activity. The Corona epidemic, combined attendance, and the incompatibility of the annual curriculum with the wishes of the students are the most important threats to sports activity.